Long-Term Mental Health Problems After Delirium in the ICU*. Issue 10 (October 2016) - Wolters, Annemiek E.; Peelen, Linda M.; Welling, Maartje C.; Kok, Lotte; de Lange, Dylan W.; Cremer, Olaf L.; van Dijk, Diederik; Slooter, Arjen J.C.; Veldhuijzen, Dieuwke S.
Abstract : Objectives: To determine whether delirium during ICU stay is associated with long-term mental health problems defined as symptoms of anxiety, depression, and posttraumatic stress disorder. Design: Prospective cohort study. Setting: Survey study, 1 year after discharge from a medical-surgical ICU in the Netherlands. Patients: One-year ICU survivors of an ICU admission lasting more than 48 hours, without a neurologic disorder or other condition that would impede delirium assessment during ICU stay. Interventions: None. Measurements and Main Results: One year after discharge, ICU survivors received a survey containing the Hospital Anxiety and Depression Scale with a subscale for symptoms of depression and a subscale for symptoms of anxiety, and the Impact of Event Scale 15 item measuring symptoms of posttraumatic stress disorder. Participants were classified as having experienced no delirium ( n = 270; 48%), a single day of delirium ( n = 86; 15%), or multiple days of delirium ( n = 211; 37%) during ICU stay. Log-binomial regression was used to assess the association between delirium and symptoms of anxiety, depression, and posttraumatic stress disorder. The study population consisted of 567 subjects; of whom 246 subjects (43%) reported symptoms of anxiety (Hospital Anxiety and Depression Scale with a subscale for anxiety, ≥ 8), and 254 (45%) symptoms of depression (Hospital Anxiety and Depression Scale with a subscale for depression, ≥ 8). In 220 patients (39%), the Impact of Event Scale 15 item was greater than or equal to 35, indicating a high probability of posttraumatic stress disorder. There was substantial overlap between these mental health problems—63% of the subjects who scored positive for the presence of any three of the mental health problems, scored positive for all three. No association was observed between either a single day or multiple days of delirium and symptoms of anxiety, depression, or posttraumatic stress disorder. Conclusions: Although symptoms of anxiety, depression, and posttraumatic stress disorder were found to be common 1 year after critical illness, the occurrence of delirium during ICU stay did not increase the risk of these long-term mental health problems. Abstract : Supplemental Digital Content is available in the text.